Influence Mix Marketing Against Room Sales Volume at the Harmoni Indragiri Hotels - Rahmawaty, Nina; Mandataris (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
The purpose of the study article is to give information related to the efforts of a moving company in the field of hospitality through mixed marketing to increase the sales volume of service rooms. Retrieval method sample ie using accidental sampling with a total of 93 respondents. Data analysis through regression testing simple and regression multiple with the use of partial tests that include product, price, place, and promotion influential in a way positive to sales volume. As well the use of simultaneous tests is influential in a way positive to sales volume. Dominant products and prices have the biggest influence. Whereas promotion has the least influence. This means that the Company must more pay attention to the section promotion for maximum promotion of the hotel to the market to increase it more known and familiar so consumers at the moment will look for hotels already directly Imagine the Harmoni Indragiri hotel for become choice main.